The Extended Barthel Index (EBI) can Be Reported as a Unidimensional Interval-Scaled Metric – A Psychometric Study - Maritz, Roxanne; Tennant, Alan; Fellinghauer, Carolina Saskia; Stucki, Gerold; Prodinger, Birgit; on behalf of the NRP74 StARS clinics (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2019)
Background The Extended Barthel Index (EBI), consisting of the original Barthel Index plus 6 cognitive items, provides a tool to monitor patients’ outcomes in rehabilitation. Whether the EBI provides a unidimensional metric, thus can be reported as a valid sum-score, remains to be examined.Objective To examine whether the EBI can be reported as unidimensional interval-scaled metric for neurological and musculoskeletal rehabilitation.Methods Rasch analysis of a calibration sample of 800 cases from neurological or musculoskeletal rehabilitation in 2016 in Switzerland.Results In the baseline analysis no fit to the Rasch Model was achieved. When accommodating local dependencies with a testlet approach satisfactory fit to the Rasch Model was achieved, and an interval scale transformation table was created.Conclusion The results support the reporting of adapted EBI total scores for both rehabilitation groups by applying the interval scaled transformation table presented in this study.
Keywords: activities of daily living; assessment instruments; outcome assessment; rehabilitation; Rasch model; quality management